Regulating Artificial Intelligence Liability in Indonesia: A Normative Analysis of Accountability in Autonomous Decision-Making Systems - Febryan Hidayat; Ihsan Ihsan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid integration of artificial intelligence (AI) into Indonesian society raises critical challenges for legal accountability, particularly in autonomous decision-making systems where traditional civil law frameworks are insufficient. This study employs a normative-analytical methodology, combining doctrinal review of Indonesian statutes, judicial rulings, and ministerial regulations with empirical examination of court cases and comparative analysis of international AI governance models. Findings indicate that liability in practice is mediated primarily through human actors and institutions, revealing interpretive gaps, procedural inconsistencies, and socio-legal constraints in judicial enforcement. Normative-comparative analysis demonstrates that hybrid liability models—combining strict liability for high-risk AI and fault-based responsibility for routine applications—can reconcile domestic law with global best practices, while sector-specific recommendations emphasize human oversight, transparency, and institutional accountability. The study provides a cohesive framework for AI liability, integrating doctrinal, empirical, and ethical considerations to guide legislative reform, judicial interpretation, and policy implementation. These findings advance both theoretical understanding of AI responsibility in civil law jurisdictions and practical guidance for the regulation of autonomous systems in emerging economies.